A MULHER DE JÓ: UM GRITO CONTRA A TEOLOGIA DA RETRIBUIÇÃO. Uma análise exegética de Jó 1,1-2,13. - WALDHELm, Wellington da Cunha (2015)
The book of Job belongs to the wisdom literature of Israel. Its content is a big debate among scholars. These formed an educated segment of the population: read and write. Wisdom was too valued and seen as prudent guidance for life. The Job 1-2 text belongs to the part of the book frame with Chapters 42.12-17. These frames were not born in the book was probably written in the fifth century BC, in the post-exilic period, during the rule of the Persians. But probably born in the tenth century BC Since its greatest value occurred at the junction of its history in the post-exile since the Persian empire brought profound changes to the lives of the people in Judah. Despite the apparent tolerance on the part of their leaders, they They have created very effective methods to achieve their goals on the subject peoples. Through a strong bureaucracy, fiscal and military controlled and guaranteed the order and the payment of taxes. The temple became the intermediary between the empire and the people. The economy and society were structured as the Persian tax regime. This economic and administrative policy favored the enrichment of the dominant sectors, and consequently the increasing impoverishment of the peasantry. The priests were leaders of the people and the theology of retribution became very strong at that time. It is from experience and observation of reality that comes from a resistance movement to the theology of retribution. At that moment stand women who courageously open their mouths and impose themselves in front of an oppressive view of Judah Temple who was abusing offers so that this form of billing could pass on the taxes owed to the empire. In chapter 2.9, Job's wife screams against this oppression before an abusive theology, leaving their mark here for the story that something was wrong in the post-exilic religion. His intention is to show that text through reality because they do not agree with the statements of the priests of the temple who hold this theology, on the infallible punishment for the rich wicked and the suffering of the poor and of women as punishment indication. KEYWORDS: Job,